Osseodensification versus piezoelectric internal sinus elevation (PISE) technique in delayed implant placement (a randomized controlled clinical trial) - Mohammed Samir; Mohamed Wagdy Bissar; Hala Ahmed Abuel-Ela (BMC, 2024)
Abstract Transalveolar sinus elevation is a minimally invasive technique aimed at augmenting the vertical bone height in the posterior maxilla, facilitating successful implant placement in areas with insufficient bone volume. This study compares the efficacy of osseodensification and piezoelectric internal sinus elevation (PISE) techniques in delayed implant placement. The primary objective was to radiographically assess vertical bone gain and bone density, while secondary objectives included clinical assessment of primary implant stability and post-operative satisfaction of both patients and operators. The study population of a total of 16 patients was randomly divided into two groups. Group 1 underwent osseodensification sinus lift using sticky bone as a graft material, whereas Group 2 received PISE with the same graft material. Results indicated that the osseodensification technique led to greater bone gain, improved bone density, and shorter surgical duration. Additionally, osseodensification was associated with enhanced rapid healing and higher patient satisfaction. Conversely, the PISE technique demonstrated superior primary stability of implants on the day of surgery. These findings suggest that while both techniques are effective, osseodensification may offer advantages in terms of bone gain, density, and patient satisfaction, making it a reliable method for enhancing rapid healing in delayed implant placement. the study was registered on clinicaltrials.gov at 26th September 2023 and clinical trials ID is NCT06055127.